Honorary Doctorate Dr. Katalin Karikó, 20th of October 2022 - Karikó, Katalin 1955- (Doctor Honoris Causa Series / Faculty of Science, Radboud University, 2023)
On 20 October 2022, the day that Radboud University celebrated its 99th anniversary, Dr. Katalin Karikó received a Radboud honorary doctorate in recognition of her scientific contributions to developing mRNA-based vaccines. This edition includes the laudatio of the honorary supervisor and the speech of the honorary doctor.Karikó spent years researching medical applications of mRNA. Her dream was to develop synthetic mRNA and use this to cure cancer, strokes, and influenza. Eventually, after years of toil, rejection, and criticism from colleagues, she and fellow researcher Drew Weissman demonstrated that it is possible to trigger an immune response in the body with mRNA without the body turning against the mRNA itself. With this breakthrough, a new revolutionary technique was born.Thanks to Karikó's scientific work, BioNTech/Pfizer and Moderna were able to develop the current mRNA vaccines against COVID-19. A prime example of the beneficial impact that fundamental research can eventually have on society. Honorary supervisor Floris Rutjes, Professor in Organic Synthesis: "With courage and determination, she pursued her scientific vision for a very long time, and by doing so, she has ultimately made a significant contribution to the fight against viral diseases."